Gender divides in teachers' readiness for online teaching and learning in higher education: Do women and men consider themselves equally prepared?. (July 2023) - Scherer, Ronny; Siddiq, Fazilat; Howard, Sarah K.; Tondeur, Jo
Abstract: During the last years, the "Great Online Transition" has brought to light large variation in teachers' readiness for online teaching and learning (OTL). Drawing from an international sample of 731 higher-education teachers, we examined gender differences in OTL readiness as a source of this variation. Currently, in the field of OTL, better evidence is needed to understand the associated dimensions and effects of gender on teachers' experiences and perceptions of readiness, to provide better support and professional learning opportunities in transitioning to an online and blended practice. To provide such evidence, we first evaluated the measurement bias in the readiness measures and found support for strong gender invariance. Second, we quantified the gender differences in readiness levels: Women reported higher readiness for cognitive activation practices ( d  = +0.15); men reported higher self-efficacy in technological content knowledge ( d  = −0.20). These gender differences were small, varied across readiness constructs, and were due to a gender gap in OTL experience. Third, construct associations involving perceived institutional support were weaker for women. To improve the quality, robustness, and validity of the respective evidence, we argue that studying gender divides in OTL readiness needs to consider measurement bias, OTL experience, and construct associations. Highlights: Readiness measures were largely gender-invariant, allowing for mean comparisons. Yet, some readiness indicators showed measurement bias across gender. Women reported lower TCK self-efficacy and better online teaching presence. Gender differences in readiness constructs were partly explained by OTL experience. For men, institutional support was more closely related to other readiness constructs.